Biochemical screening of the domestic and world prosa millet collection on the content of amilose in grain (Experimental biology, 2018)
Amylose is the most important biochemical indicator of grain quality in cereals. In this research are presented the results of biochemical screening for the quantitative amylose content in grain of 112 proso millet samples domestic and world collections (Afghanistan, Belgium, Hungary, China, Canada, India, Iran, Mexico, Pakistan, Russia, USA, Turkey, Ukraine, France). On the basis of the obtained data was made conditional classification of proso millet collection on amylose content. The results of biochemical screening of proso millet genotypes showed that the studied samples have different by the amylose content and their number varied from 5.5 to 34.90%. In domestic samples the amylose content ranged from 14.6% to 34.8%. A low amylose content were shown samples K-3742, PI 436626 (Lung Shu 18), PI 436625 (Lung Shu 16) and Ma zha Yan, averaging from 5.5 to 5.9%. Selected samples represent valuable genetic material for the creation of glutinous proso millet varieties and will be involved in the breeding process. On the basis of the conditional classification, it was found that the amylose content was higher than 25% (high amylose) in 68% of the studied samples , 23% were medium-amylose (15-25%) groups, and only 5% and 4% were low-amylose (6-14%) and glutinous (to 6%) groups, respectively.Key words: millet, collection, amylose, screening, classification.